Anatomy of the sacroiliac joints in children and adolescents by computed tomography. Issue 1 (December 2017) - Zejden, Anna; Jurik, Anne
Abstract Background Diagnosing sacroiliitis by magnetic resonance imaging (MRI) in children/adolescents can be difficult due to the growth-related changes. This study analyzed the normal osseous anatomy of the sacroiliac joints (SIJ) in a juvenile population using computed tomography (CT). Methods The anatomy of the SIJ was retrospectively analyzed in 124 trauma patients aged 9 months – <18 years by CT, based on 2 mm slices in axial, semi-axial and semi-coronal planes. The following anatomical features were recorded: intersegmental fusion of the sacral vertebral segments 1–3 (S1-S3), ossified nuclei (antero-superior at S1, lateral to the intervertebral spaces and lateral to S1 and S2) and joint facet defects larger than 3 mm. Results Fusion of S1/S2 started at the age of 6 years and was complete after the age of 13 years in most girls and after the age of 14 years in most boys. Fusion of S2/S3 started at the age of 9 years, but could remain incomplete up to 18 years in both genders. Ossified nuclei antero-lateral at S1 and/or in the joint space were observed until the age of 18 years and occurred in 77% of individuals ≥13 years with intraarticular localization in 64% of girls and 60% of boys. Joint facet defects >3 mm occurred in 21 children/adolescents (17%) located to both the iliac and sacral joint facets. Conclusions Normal osseous SIJ structures in children and adolescents vary considerably. Attention to these normal anatomical structures during growth may help to avoid false positive findings by MRI.